High-intensity transcranial alternating current stimulation combined with pharmacotherapy for adolescent major depressive disorder: a prospective case report study - Yuan, Ziyi; Hu, Ying; Cheng, Dandan; Yang, Yilin; Hong, Su; Kuang, Li (Frontiers in Psychiatry, 2025)
BackgroundAdolescent major depressive disorder (MDD) presents a growing public health concern due to the limited efficacy of current treatments, while high-intensity transcranial alternating current stimulation (HI-tACS) has shown promise in adults but remains unstudied in adolescents. This study therefore examined the preliminary efficacy and safety of HI-tACS combined with pharmacotherapy for first-episode adolescent MDD, with a primary focus on suicide risk reduction.MethodsIn this prospective case series, seven adolescents (aged 12–17 years) diagnosed with MDD received a 4-week intervention combining HI-tACS (77.5 Hz/15 mA, once daily for 20 sessions) with pharmacotherapy. All participants received a standardized pharmacological regimen consisting of sertraline hydrochloride with adjunctive aripiprazole, while oxazepam was permitted as needed for insomnia. Clinical outcomes were assessed at baseline, week 2, and week 4 using the 24-item Hamilton Depression Rating Scale (HAMD-24) and the Patient Health Questionnaire (PHQ-9).ResultsAfter 4 weeks of treatment, 57.1% of patients achieved a clinical response (≥ 50% reduction in HAMD-24 total score) and 14.3% reached remission (HAMD-24 total score ≤ 8). The HAMD-24 total score significantly decreased at Weeks 2 (Z = –2.366, p = 0.018) and Week 4 (Z = –2.196, p = 0.028). PHQ-9 total scores showed more pronounced improvement during the early treatment phase. Suicide risk initially declined but then rose slightly in the later phase. The intervention was well tolerated with no serious adverse events reported.ConclusionsThe combination of HI-tACS and pharmacotherapy demonstrated potential early effects in this small cohort of adolescents with MDD, particularly during the initial phase of treatment. These preliminary findings warrant further investigation through large-scale randomized controlled trials to establish efficacy and safety profiles, and to further characterize suicide risk trajectories.